인도어 무선통신시스템에서 고정적 인도어기지국 선택을 통한 자가치유 알고리즘 - 이호원; 이기송; Lee, Howon; Lee, Kisong (한국정보통신학회논문지, 2014)
In order to resolve coverage hole problems caused by indoor-BS (IBS) faults, we propose a new frame structure and practical algorithm based on optimization technique. Our main contributions can be described as follows: 1) a frame structure with healing channels for solving abnormal IBS faults; and 2) an efficient heuristic resource allocation algorithm with fixed IBS selection to reduce the complexity for the optimization problem. Through intensive simulations, we evaluate the performance excellency of our proposed algorithm with respect to average cell capacity and user fairness compared with conventional algorithms. 인도어 기지국(Indoor BS) 결함으로 인해 발생하는 커버리지홀 문제를 해결하기 위하여, 새로운 프레임 구조와 최적화 기법 기반의 실제적인 알고리즘을 제안한다. 우리의 핵심 공헌은 다음과 같다: 1) 갑작스런 IBS 결함 문제 해결을 위한 힐링(healing) 채널을 가지는 새로운 프레임 구조를 제안하고 2) 최적화 문제의 복잡도 감소를 위한 고정적 IBS 선택에 기반한 효과적인 휴리스틱 자원할당 알고리즘을 제안한다. 시뮬레이션을 통하여 평균 셀 용량과 사용자 공평성 관점에서 기존 알고리즘에 비해 제안 방안이 우수함을 증명한다.